A partner's smile is not per se a safety signal: psychophysiological response patterns to instructed threat and safety - Morato, Cristina; Guerra, Pedro; Bublatzky, Florian (Psychophysiology, 2023)
Recent studies on fear conditioning and pain perception suggest that pictures of loved ones (e.g., a romantic partner) may serve as a prepared safety cue that is less likely to signal aversive events. Challenging this view, we examined whether pictures of smiling or angry loved ones are better safety or threat cues. To this end, 47 healthy participants were verbally instructed that specific facial expressions (e.g., happy faces) cue threat of electric shocks and others cue safety (e.g., angry faces). When facial images served as threat cues, they elicited distinct psychophysiological defensive responses (e.g., increased threat ratings, startle reflex, and skin conductance responses) compared to viewing safety cues. Interestingly, instructed threat effects occurred regardless of the person who cued shock threat (partner vs. unknown) and their facial expression (happy vs. angry). Taken together, these results demonstrate the flexible nature of facial information (i.e., facial expression and facial identity) to be easily learned as signals for threat or safety, even when showing loved ones.
Online veröffentlicht: 22. Februar 2023
Gesehen am 21.08.2024